Patient and health service delay in the diagnosis of pulmonary tuberculosis in Ethiopia - Lindtjorn Bernt; Demissie Meaza; Berhane Yemane (BMC, 2002)
Abstract Background Delay in the diagnosis of tuberculosis may worsen the disease, increase the risk of death and enhance tuberculosis transmission in the community. This study aims to determine the length of delay between the onset of symptoms and patients first visit to health care (patient delay), and the length of delay between health care visit and the diagnosis of tuberculosis (health service delay). Methods A cross sectional survey that included all the public health centres was conducted in Addis Ababa from August 1 to December 31 1998. Patients were interviewed on the same day of diagnosis using structured questionnaire. Results 700 pulmonary TB patients were studied. The median patient delay was 60 days and mean 78.2 days. There was no significant difference in socio-demographic factors in those who delayed and came earlier among smear positives. However, there was a significant difference in distance from home to health institute and knowledge about TB treatment among the smear negatives. The health service delay was low (median 6 days; mean 9.5 days) delay was significantly lower in smear positives compared to smear negatives. Longer health service delay (delay more than 15 days) was associated with far distance. Conclusions The time before diagnosis in TB patients was long and appears to be associated with patient inadequate knowledge of TB treatment and distance to the health centre. Further decentralization of TB services, the use of some components of active case finding, and raising public awareness of the disease to increase service utilization are recommended.